Accuracy of radar water level measurements - Fulford, Janice M., author; Ester, Lee W., author; Heaton, John W., author; U.S. Committee on Irrigation and Drainage, publisher (Colorado State University. Libraries, 2007)
Radar water-level sensors are generating a lot of interest among hydrographers because of their ease of installation and low maintenance. However, limited information is available on the accuracy and performance of radar sensors in the field. This paper presents test results from recent field measurements made with radar water-level sensors. Field data collected with two pulse radars, (Design Analysis Associates H-3611 and the Ohmart Vega Puls 62) and one continuous wave frequency modulated radar (Saab Rosemount) during lake drawdown at Horse Mesa Dam, Arizona, are presented and compared against a conventional float-well system. (The use of firm, trade and brand names in this report is for identification purposes only and does not constitute endorsement by the U.S. Government). Measured radar data were analyzed for possible sources of systematic measurement uncertainty (error) including sensor height above water (air gap), air temperature and surface waves. The Ohmart Vega sensor has a systematic uncertainty from varying air gap. The H-3611 and the Saab Rosemount sensor do not have an obvious systematic uncertainty from varying air gap. None of the radar sensors have an obvious uncertainty from surface waves when compared with the float-well systems. No systematic uncertainty due to temperature or wind speed was noted for any of the radars. Analysis of the field data indicate that the data measured by the H-3611 and the Saab Rosemount are not statistically different from that collected by the float-well system. For the data measured by the Ohmart Vega, a systematic error of about 0.3 ft over a 35-ft change in water level occurred during the field measurements.
USCID fourth international conference
Not digitized by CSUL Digital Services.
Presented at the Role of irrigation and drainage in a sustainable future: USCID fourth international conference on irrigation and drainage on October 3-6, 2007 in Sacramento, California.